2017
DOI: 10.5897/ajmr2017.8481
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility patterns of Staphylococcus aureus and coagulase negative staphylococci isolated from humans in Nairobi, Kenya

Abstract: Nosocomial infections due to multidrug resistant Staphylococcus aureus are an important health problem worldwide. Antimicrobial resistance prolongs the duration of hospitalization, thereby increasing the cost of patient care. For a long time, methicillin was considered as drug of choice for treatment of penicillin-resistant staphylococcal infections. Emergence of methicillin resistance reduced the available options for treatment of nosocomial and community acquired S. aureus. Normally, such strains are only se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
3
2
1
Order By: Relevance
“…A somewhat lower but substantial proportion of S. aureus isolates (35%) were resistant to one or more tetracyclines, another commonly used class of antimicrobials. This is consistent with findings from other studies that reported levels ranging from 15.5% to 53.4% (Omuse, Kabera & Revathi, 2015;Sangeda et al, 2017;Wangai et al, 2019).…”
Section: (B) S Aureussupporting
confidence: 93%
See 3 more Smart Citations
“…A somewhat lower but substantial proportion of S. aureus isolates (35%) were resistant to one or more tetracyclines, another commonly used class of antimicrobials. This is consistent with findings from other studies that reported levels ranging from 15.5% to 53.4% (Omuse, Kabera & Revathi, 2015;Sangeda et al, 2017;Wangai et al, 2019).…”
Section: (B) S Aureussupporting
confidence: 93%
“…aureus was the most frequently isolated Gram positive organism, mostly from bloodstream infections and wounds or abscesses, consistent with the findings of other studies (Omuse, Kabera & Revathi, 2015;Sangeda et al, 2017;Wangai et al, 2019). The reported prevalence of MRSA among S. aureus isolates has been quite variable across Africa (Kesah et al, 2003;Falagas et al, 2013), as well as between different facilities within Kenya (Omuse, Kabera & Revathi, 2015;Sangeda et al, 2017;Wangai et al, 2019;Iliya et al, 2020).…”
Section: (B) S Aureussupporting
confidence: 91%
See 2 more Smart Citations
“…Antibiotic resistant bacteria have been observed widely in aquatic environments following antibiotic contamination from wastewater treatment plants or agricultural runoffs (Schmieder & Edwards, 2012). Avoparcin is a glycopeptide antibiotic that is chemically very similar to vancomycin; there have been earlier concerns about the use of avoparcin in agriculture in various countries as well as Kenya (Bager, Madsen, Christensen, & Aarestrup, 1997; Nilsson, 2012; Raphael, Sam, Anne, Peter, & Samuel, 2017), and it would be reasonable to think it would be the cause of vancomycin resistance gene clusters in coastal waters.…”
Section: Discussionmentioning
confidence: 99%